Success and Failure of Reform : Isights from the Transition of Agriculture - Rozelle, Scott; Swinnen, Johan F.M. (American Economic Association, 2016)
The paper analyzes the linkages between the reform strategies in transition countries and economic performance. We focus on agriculture because of the sharpness of the policy changes, fundamental differences among countries, and relative simplicity of agricultural relationships. We document post reform performance in the transition countries of Asia and Europe. We show how: a.) pricing reform and subsidy reductions; b.) land rights reform and policies that affect farm restructuring; and c.) the presence institutions that facilitate exchange (either markets or market substitutes) affect output and productivity. The paper ends with general lessons on reforms and transition.